Development of an ex vivo assay for the characterization of a new elastin-like polymer with antimicrobial properties - da Costa, A. (2013)
[Excerpt] New treatment formulations for skin regeneration and wound infectionshaverecentlybeenthefocusofresearchinthebiomedical ﬁeld,as they are one of the most common healthcare-associated infections. Antimicrobial peptides (AMPs) are a class of small molecules that can be used in the treatment of skin and wound infections as they occur as part of the innate defense mechanism in many organisms, even in microbes and virus, displaying immunomodulatory effects. With advances in protein engineering and recombinant DNA technology, it is now possible to reengineer protein-based materials with added functionality.Indeed,recombinantDNAtechnologyallows combining in the same molecule distinct functionalities, leading to the production of a chimeric protein displaying the properties of each blockof amino acids. With the aim of developing novel advanced materials and ultimately, the fabrication of advanced medical devices, hereby we describe the development, processing and characterization of a new recombinant protein-based-polymer (rPBP) with antimicrobial activity. The functionalrPBPcomprisesafunctionaldomainbasedonasyntheticcationic AMP, fused in frame with an elastin-like-polymer consisting of 200 repeatsofVPAVG(A200),asstructural unit.